1993
DOI: 10.1073/pnas.90.5.1721
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of variable region 3 sequences of human immunodeficiency virus type 1 from infected children with the RNA and DNA sequences of the virus populations of their mothers.

Abstract: We have compared the variable region 3 sequences from 10 human immunodeSciency virus type 1 (H1V-1)-infected infants to virus sequences from the corresponding mothers. The sequences were derived from DNA of uncultured peripheral blood mononuclear cells (PBMC), DNA ofcultured PBMC, and RNA from serum collected at or shortly after delivery. The infected infants, in contrast to the mothers, harbored homogeneous virus populations. Comparison of sequences from the children and clones derived from DNA of the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
135
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 19 publications
20
135
3
Order By: Relevance
“…Coffin 21 has estimated that, on average, a mutation occurs several times daily at every position in the HIV-1 genome. Although minimal genotypic heterogeneity has been described in even highly variable regions (such as the V3 region of the envelope protein 22,23 ) of isolates obtained in early maternally acquired infection, our data suggest that by the age of two to three months diversification may have occurred to such a degree that mutations conferring resistance to antiretroviral drugs were present before therapy and were selected during therapy.…”
Section: Discussionmentioning
confidence: 75%
“…Coffin 21 has estimated that, on average, a mutation occurs several times daily at every position in the HIV-1 genome. Although minimal genotypic heterogeneity has been described in even highly variable regions (such as the V3 region of the envelope protein 22,23 ) of isolates obtained in early maternally acquired infection, our data suggest that by the age of two to three months diversification may have occurred to such a degree that mutations conferring resistance to antiretroviral drugs were present before therapy and were selected during therapy.…”
Section: Discussionmentioning
confidence: 75%
“…MTCT occurs in utero, during delivery, and through breastfeeding, at a rate of approximately 30% in the absence of antiretroviral therapy (6,19). Previous studies have demonstrated that, despite a complex viral population in the mother, only viruses of a restricted subset were typically transmitted to the infant (1,23,29,40,41,45,48). This suggests that some viruses may be favored for transmission in this setting.…”
mentioning
confidence: 97%
“…In the context of this direction of viral spread, the villous syncytiotrophoblast-cytotrophoblast layer forming the maternal-fetal interface would be expected to play a critical role in modulating virus spread to the fetus. Recently, three different groups have used PCR to study possible HIV nucleotide sequence determinants common to viruses being transmitted to offspring (Wolinsky et al, 1992;Scarlatti et al, 1993;Mulder-Kampinga et al, 1993). All three studies reveal a homogeneous population of HIV-1 in the fetus and early neonate as compared with the mother, suggestive of a certain degree of selectivity of the transmission event, possibly during the first or Short communication Overall nucleotide sequence identity is 89 % between the two LTR fragments used in the reporter constructs.…”
mentioning
confidence: 99%